An entrepreneurial finance study: MSME performance based on entrepreneurial and financial dimensions - Maria Rio Rita; Mohamad Nur Utomo (University of Merdeka Malang, 2019)
Various researches have been conducted towards the dynamics of micro, small, and medium enterprise (MSME) developments, but there are still research gaps that can be explored further. The purpose of this research is to examine the determinant factors of MSME performance as seen from the entrepreneurial dimension and the financial activities done by entrepreneurs. The research objects of this study are two batik MSME centers in Central Java Province, which are Rembang Regency and Surakarta municipality. The research model was tested by using PLS-SEM with WarpPLS version 6.0. The research findings revealed there is a positive influence between the dimensions of entrepreneurship and outside finance, entrepreneurial dimension and MSME performance, outside finance, and MSME performance, as well as innovation investment and MSME performance. Another research finding found that the entrepreneurial dimension, which consists of entrepreneurial emotion and entrepreneurial cognition, does not have a positive influence on MSME performance. Meanwhile, outside finance has a negative influence on innovation investment. This research proposes a future research agenda to add other variables that are suspected of influencing MSME performance, whether from a financial or a non-financial aspect, such as financial literacy and the application of digital marketing.JEL Classification: A10, D19, G40DOI: https://doi.org/10.26905/jkdp.v23i2.3076